A new contact & slip model for tracked vehicle transient dynamics on hard ground. (October 2017) - Özdemir, Mehmet Nuri; Kılıç, Varlık; Ünlüsoy, Y. Samim
Highlights: General transient contact and slip model for tracked vehicles on hard ground. Transient slip displacement-shear stress model with new accurate contact time calculation method. Vertical contact force calculation taking into account track pretension and variations. Shear stress and force calculations under track pads. Test simulation verification and parameter sensitivity of the theoretical model. Abstract: This study presents a new general transient contact and slip model for tracked vehicles on hard ground which is simple, accurate, and in agreement with the test results to a satisfactory level. Simulating zero track speed instances become possible with the new contact/shear model which is the major proposed improvement in addition to more accurate results for transient steering and tractive inputs. The model represents a general tracked vehicle having rear or front sprockets, with parameters for center of gravity, wheel positions, number of wheels, and track-pretention. To calculate longitudinal and lateral forces, a transient shear model is used. Shear stress under each track pad is assumed to be a function of shear displacement. The contact time formulation used in shear displacement calculation is improved to gain accuracy for transient and zero track speed conditions. The model is implemented on the Matlab/Simulink platform and verified with a comprehensive program of road tests composed of transient steering and tractive/braking scenarios. The results of the simulations and the road tests are satisfactorily similar for both constant and transient input maneuvers. Moreover, sensitivity simulations for vehicle parameters are conducted to show that the model responses are inline with the expected vehicle dynamics behaviours.